Limit analysis of multi-ring masonry arches: a parametric study on the effects of friction angle, geometry, interlocking, and ring number - Nela, Bledian; Pingaro, Marco; Trovalusci, Patrizia; Pasca, Monica (Frontiers in Built Environment, 2023)
The majority of built heritage covering large spans are built with curved masonry components, such as multi-ring arches, to attain greater overall thickness. Their ultimate structural capacity when subjected to external loads is significantly influenced by the various construction techniques utilized. Such structures are made up of independent rings that communicate with one another through interface contacts, and the geometrical features, like size, orientation and arrangement of units play a significant role as well as the mechanical characteristic, like friction. Multi-ring arches subjected to a vertical load at quarter span are assessed utilizing an in-house code implementing the upper bound approach of the limit analysis for masonry structures. A discrete model has been adopted accounting for a combination of size and disposition of blocks, friction angle, number of rings and the span length are taken into account. Following their combination of impacts in terms of collapse multipliers, which are classified as per respective influencing parameters, each one's importance is demonstrated. It is further shown that the interlocking effect from the placement of units and the friction angle affect the overall structural behavior for different spans and varied shapes.